PENINGKATAN HASIL BELAJAR PEMBUATAN HIASAN BUSANA MELALUI PENERAPAN MEDIA YOUTUBE DI SEKOLAH MENENGAH KEJURUAN - Winda Saputri (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2019)
The purpose of this study was to find out (1) the application of internet media and (2) to increase the learning outcomes of fashion decoration subjects through the application of internet media. This type of research is classroom action research. Data collection techniques use observation techniques, field notes, performance tests, and documentation. The data analysis technique uses quantitative descriptive analysis techniques. The results of this study indicate that (1) the application of internet media is carried out through planning, implementation and evaluation activities. (2) The application of internet media can improve the learning outcomes of making fashion ornaments. The average ability of learning outcomes for making fashion ornaments in pre-action is 54% with sufficient categories, increasing in the first cycle to 70.50% with good categories and increasing in the second cycle to 78.33% in the very good category.